Strategies for Improving pedagogical Competence of Islamic Religious Education Teachers in Junior Secondary Schools - Dendi Marno (Program Pascasarjana UMSB, 2022)
Teacher competence is an important part that can be an indicator of achieving educational goals. To date, there are several problems related to the pedagogical competence of teachers in various educational institutions. Therefore, this study aims to reveal how strategies for improving the pedagogical competence of teachers in schools. The research was conducted with a qualitative approach, data were collected by observation techniques, interviews and documentation studies. The informants of this study were teachers at the First Menegah Negeri School 6 Koto XI Tarusan, additional data obtained from the principal and teachers of Islamic religious education. The findings of this study are that the principal of the first menegah school of the country 6 Tarusan set several policies related to increasing teacher competence, the policy taken was to send Islamic religious education teachers to be active in workshops, attend seminars, workshops. In accordance with the policy set by the principal, it is known that the teacher of Islamic religious education at the State Junior High School 6 Koto XI Tarusan has good pedagogic competence. The recommendation of this study is that the principal as the leader of each educational institution must increase his attention in improving the competence of teachers in the educational institution he leads.